Navigating the Nexus of Cyber-Physical Connectivity: A Multi-Criteria Policy Framework for Strategic Governance and Infrastructure Resilience - Dr. Alistair Sterling (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
The rapid digitization of critical national infrastructure has created a paradox where increased connectivity facilitates economic efficiency but simultaneously introduces systemic vulnerabilities. This research explores the intersection of strategic cybersecurity governance, multi-criteria decision analysis (MCDA), and holistic risk governance. By synthesizing recent high-profile breaches, such as the MediSecure and Colonial Pipeline incidents, with foundational theories of public policy analysis and cost-benefit methodologies, the study proposes a comprehensive framework for protecting essential services. The analysis delves into the "connectedness" problem, arguing that safety and security risks can no longer be managed in silos. Using a policy-led approach to infrastructure appraisal, the article examines how regulatory codes-particularly within the EU electricity sector and financial services-act as pivotal mechanisms for risk mitigation. The research further evaluates the role of advanced blockchain methodologies and artificial intelligence in augmenting data privacy protocols for decentralized assets like cryptocurrencies. By applying the OECD reference checklist for regulatory decision-making, the study identifies critical gaps in current governance structures, specifically regarding the "econocracy" of policy evaluation versus holistic governance perspectives. The findings suggest that a risk-based policy framework, supported by rigorous vulnerability assessments and penetration testing, is essential for maintaining trust in digital ecosystems. This article provides an extensive theoretical elaboration on the necessity of integrated risk governance, advocating for a transition from managerialism to a multi-criteria, participatory approach in safeguarding the Union’s digital sovereignty.